Responses of Three Bromegrass (Bromus) Species to Defoliation under Different Growth Conditions - B. Biligetu; Bruce Coulman (International Journal of Agronomy)
Bromegrass species are important forage crops in temperate regions of world. This study compared responses of three bromegrass species to defoliation in the greenhouse and field to determine if the former could predict responses in the latter. Experiments were conducted in 2006 and 2007 in Saskatoon (52°07′ N, 106°38′ W), Canada on meadow bromegrass (Bromus riparius Rehm.), smooth bromegrass (Bromus inermis Leyss.), and hybrid bromegrass (B. riparius X B. inermis) following defoliation to 5 cm stubble height. When defoliated at the vegetative stage, above-ground biomass was similar among the three species in the field, but meadow bromegrass produced greater above-ground biomass than smooth bromegrass in the greenhouse. When defoliated at the stem elongation stage, meadow bromegrass produced greater above-ground biomass than smooth bromegrass in both environments. In the field, for all defoliation treatments, tiller number was greatest in meadow bromegrass, intermediate in hybrid bromegrass, and least in smooth bromegrass. In the greenhouse, however, the three species did not differ in tiller number. Similar results were found for below-ground biomass. Thus, testing the effect of defoliation in the greenhouse environment did not accurately predict the effect in the field environment.